Environmentally Friendly Application to Green Open Space on the banks of the Kayan River, Tanjung Selor Arab Village Kalimantan Utara Province - Eko Wahyudi*; Masruri Masruri (Universitas Syiah Kuala, 2023)
Green Open Space (RTH) is one of the important components of the environment as the main element of urban spatial planning which has a major influence on people's welfare. One type of urban green open space that must be maintained is river border green open space on the banks of the Kayan River, Tanjung Selor, Bulunagan Regency, North Kalimantan Province. Riparian zone is a buffer zone between aquatic ecosystems (rivers) and land. This is what efforts are made to create green open spaces that are environmentally friendly.In general, this study aims to find out how to apply environmentally friendly green open spaces on the banks of the Kayan River, Tanjung Selor Arab Village, North Kalimantan Province.The method in this study included direct observation of the spaciousness of the existing green open space conditions on the banks of the Kayan River, especially in the Arab village area, as well as direct observation at several predetermined points, namely: parking circulation, garbage disposals and lighting.The results of this study note that there is a need for improvements both physically and non-physically related to existing infrastructure on the banks of the Kayana River so that environmentally friendly applications are fulfilled.